2017
DOI: 10.1002/jcb.26060
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional Interaction Between miR‐450a‐5p and miR‐28‐5p and STAT1 mRNA Triggers Osteoblastic Differentiation of Human Mesenchymal Stem Cells

Abstract: We demonstrate that the interaction between miR-450a-5p and miR-28-5p and signal transducer and activator of transcription 1 (STAT1) mRNA correlates with the osteoblastic differentiation of mesenchymal stem cells from human exfoliated deciduous teeth (shed cells). STAT1 negatively regulates runx-related transcription factor 2 (RUNX2), which is an essential transcription factor in this process. However, the elements that trigger osteoblastic differentiation and therefore pause the inhibitory effect of STAT1 nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 55 publications
0
27
0
2
Order By: Relevance
“…It has been confirmed that the abnormal expression of miRNAs is closely related to stem cell differentiation [37]. For instance, miR-34a, miR-450a-5p, and miR-28- 5p have been revealed to be involved in regulating the osteoblastic differentiation of mesenchymal stem cells [38,39]. In BMSCs, the adipogenic and osteogenic differentiation can also be regulated by miR-383 [40], miR-20a-5p [41], and miR-20a-5p [41].…”
Section: Discussionmentioning
confidence: 92%
“…It has been confirmed that the abnormal expression of miRNAs is closely related to stem cell differentiation [37]. For instance, miR-34a, miR-450a-5p, and miR-28- 5p have been revealed to be involved in regulating the osteoblastic differentiation of mesenchymal stem cells [38,39]. In BMSCs, the adipogenic and osteogenic differentiation can also be regulated by miR-383 [40], miR-20a-5p [41], and miR-20a-5p [41].…”
Section: Discussionmentioning
confidence: 92%
“…MiR‐145‐5p expression was decreased during osteogenic differentiation, and transfection of miR‐145 mimics in pluripotent mesenchymal precursor cells reduced the expression of osteogenic differentiation markers . The undifferentiated interaction networks of mesenchymal stem cells exhibited an increased miR‐145‐3p identification . In human osteoblast‐like MG‐63 cells, suppression of miR‐145 could stimulate the expression of osteoprotegerin, a soluble glycoprotein that reduced bone resorption and enhances bone formation .…”
Section: Discussionmentioning
confidence: 99%
“…16 The undifferentiated interaction networks of mesenchymal stem cells exhibited an increased miR-145-3p identification. 29 In human osteoblast-like MG-63 cells, suppression of miR-145 could stimulate the expression of osteoprotegerin, a soluble glycoprotein that reduced bone resorption and enhances bone formation. 30 MiR-145 also negatively affected the osteoblastic differentiation by targeting Cbfb, the transcription factors that are essential for bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are 18–25 nucleotide noncoding RNAs that suppress the translation and stability of their target mRNAs generally through imperfect base‐pairing binding to the 3′ untranslated regions (3′ UTRs) of these target mRNAs (Rana, ). Research has increasingly suggested that diverse microRNAs (miRNAs) participate in numerous biological processes such as embryo development, stem cell pluripotency, differentiation, cell proliferation and apoptosis (Chen et al., , Dernowsek et al., ; Liu, Zhang, Sun, Su, & You, ; Wang et al., ; Zhang, Wang et al. ), but the functioning patterns and target genes of most miRNAs are still unknown.…”
Section: Introductionmentioning
confidence: 99%